Customer Decisions, WOM, and Innovation Products: The Role of Destination Servicescape as an Intervening - Toyibatul Masruroh; Yudha Trishananto (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Based on the research conducted and what you want to research about the effect of word of mouth and product innovation on customer decisions with the destination servicescape as an intervening variable. The method of this study is quantitative, with data collection techniques using questionnaires and data analysis techniques from this study using the SPSS 22 program. The results of the analysis of the research show that word of mouth has a significant positive effect on the destination servicescape. Product innovation has a significant positive effect on the destination servicescape. Word of mouth has a significant positive effect on customer decisions. Product innovation has a negative and insignificant effect on customer decisions. Destination servicescape has a significant positive effect on customer decisions. Destination Servicescape can mediate the influence of word of mouth on customer decisions. Destination servicescape can mediate the influence of Product Innovation on customer decisions.